Sejarah Undang-Undang ITE: Periodisasi Regulasi Peran Negara dalam Ruang Digital - Ramadoni, Sofwan Rizko; Gegana, Reza Pramasta; Sanata, Kalen (Jurusan Pendidikan Ilmu Pengetahuan Sosial FKIP Universitas Mulawarman, 2023)
The state inherently played a significant role in the defined digital space governed by various regulations related to telematics. From 2008 to 2024, there were three amendments to the Electronic Information and Transactions Law, each of which had implications for the state's role in the digital realm. The purpose of this article was to elucidate the changes in the state's role in the digital space resulting from alterations in the legal framework of the Electronic Information and Transactions Law. This socio-legal research employed a historical legal approach and discourse analysis concerning the periodization of the development of the Electronic Information and Transactions Law. The findings indicated that the background of changes in the state's role in the digital space was a response to various telematics phenomena that had evolved in society. Currently, there has been a strengthening of the state's role in the digital realm, including measures such as digital access termination for violators of digital rights and extensive supervision of electronic system providers.